Microepidemia de histoplasmose no município de Arapeí, São Paulo - Pardini Vicentini-Moreira, Adriana; Sayuri Kohara, Valdelene; Noroha Passos, Angela; dos Santos Feliciano, Regiane; Cupertino Barreto, Lucia; Santos de Freitas, Roseli; BD Vilela Santos, Maria Angela; Andraus Garcia, Maria Cristina (BEPA. Boletim Epidemiológico Paulista, 2008)